Dual Repurposing of End-of-Life BWRO Membranes: Ultrafiltration Membranes for Advanced Wastewater Treatment and Cation Exchange Membranes for Fungal Microbial Fuel Cells - Anissa Somrani; Mehri Shabani; Zaineb Mohamed; Kholoud Abohelal; Salam S. Alsharari; Ahmed Hannachi; Noreddine Ghaffour; Maxime Pontié (Membranes)
The objective of this study is to evaluate the degradation of end-of-life BWRO membranes sourced from a factory in France by analyzing their water permeability, roughness, and chemical composition in order to diagnose the level of degradation incurred during their first life cycle in water softening. Following this, two new applications for the end-of-life BWRO membranes were investigated: (i) as ultrafiltration membranes (UF) for domestic effluent treatment and (ii) as cation exchange membranes (CEM) for use in fungal microbial fuel cells (FMFC). The UF membrane was renovated with an acetic acid treatment and, subsequently, used for domestic effluent filtration. The cation exchange membrane was developed in two steps: (i) chlorine treatment and (ii) the deposition of an Amer Sil layer, a functional coating formed by an interpenetrating polymer network (IPN) made of sulfonated polyether sulfone (S-PES) in a cross-linked matrix of acrylic acid and divinylbenzene.